Assessing the effects of boron-doped biphasic calcium phosphate on the characteristics of chitosan-based composite foams - Acar, Nurcan; Mutlu, Busra; Akben, Hatice Kubra; Duman, Seyma (Springer, 2025)
In this study, composite foams containing chitosan (CHI) and boron doped-biphasic calcium phosphate (BCP) were developed using freeze-drying method. The quantities of BCP incorporated into the CHI matrix were introduced into the foams at three different ratios: 25 wt%, 50 wt%, and 75 wt%. The objective of this study was to investigate the microstructure, swelling, mechanical, and biological properties of boron-doped BCP/CHI-based composites. Scanning electron microscopy (SEM) micrographs revealed that all of the composites exhibited open and interconnected pore morphologies. The FTIR spectra demonstrated that boron doping interacts with the hydroxyl and phosphate groups in the CHI/BCP composites, which is evidenced by changes in peak intensities. It was found that low amounts of boron positively affected the compressive strength and in vitro cytotoxicity of the composites. Following simulated body fluid treatment, the boron-doped BCP/CHI composites exhibited robust apatite layer formation. These results indicated that the composite foams with modified physical and mechanical characteristics show considerable promise for use as composite materials in biomedical applications, including bone scaffolds or wound dressings.
Keywords: Boron; Biphasic calcium phosphate; Chitosan; Freeze-drying; Biomedical applications